2017
DOI: 10.20959/wjpps20179-10154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Medication Errors in Chemotherapy Receiving Patients in Tertiary Care Hospital

Abstract: Developing unique drug guidelines that address the institutions dose information, making drug info available electronically and train all members of the team to use electronic drug information can reduce medication error. In chemotherapy, the total no. of drugs given to the patient cannot be reduced so, there will be error occurance at some point, which is unavoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
4
1
0
Order By: Relevance
“…The common factor may be lack of adequate knowledge in PGs regarding drug therapy, lack of drug information, incorrect diagnosis, lack of patient education and poor handwriting and job related stress and work load which are the reasons for errors committed by physicians. Even similar result was observed in the study carried out by karna et al [19] conducted in medicine wards, [i.e. untrained nurses (20.3%), increased workload (37.8%), stress environment (41.7%), handwriting (43.2%), high workload (18.9%), generic drugs (13.5%), unclear order (55.5%), and wrong order (44.4%)].…”
Section: Distribution Of Medication Error Related To Professionals An...supporting
confidence: 90%
See 4 more Smart Citations
“…The common factor may be lack of adequate knowledge in PGs regarding drug therapy, lack of drug information, incorrect diagnosis, lack of patient education and poor handwriting and job related stress and work load which are the reasons for errors committed by physicians. Even similar result was observed in the study carried out by karna et al [19] conducted in medicine wards, [i.e. untrained nurses (20.3%), increased workload (37.8%), stress environment (41.7%), handwriting (43.2%), high workload (18.9%), generic drugs (13.5%), unclear order (55.5%), and wrong order (44.4%)].…”
Section: Distribution Of Medication Error Related To Professionals An...supporting
confidence: 90%
“…(73%) when compare to female (27%), (Table 1), this is because males are highly exposed to works and the chances of accidental incidents were more common which might be the reason for high number of males when compare to female. Even the similar results were observed in the study carried out by Karna et al [19] on study and evaluation of medication errors in medicine wards which showed predominant of males over females [i.e. males (77.4%) and females (22.6%)].…”
Section: Distribution Of Patients Based On Gendersupporting
confidence: 84%
See 3 more Smart Citations